Level of sexual and reproductive health knowledge and attitude among early adolescent - Abd. Aziz, Karimah Hanim; Jamani, Nurjasmine Aida; Lahasan, Nur Wajihah; Che Ujang, Syazwana Amirah; Mohd Ali Hanafiah, Nur Ili Dalia (2018)
Topic on sexual has largely remind taboo subject for discussion between parents and their children in Malaysia, which might contribute to increase activity among adolescent age group